Significant performance enhancement of yttrium-doped barium cerate proton conductor as electrolyte for solid oxide fuel cells through a Pd ingress–egress approach - Liu, Y.; Ran, R.; Li, S.; Jiao, Y.; Tade, Moses; Shao, Zongping (Elsevier SA, 2014)
Proton-conducting perovskite oxides are excellent electrolyte materials for SOFCs that may improve power density at reduced temperatures and increase fuel efficiency, thus encouraging the widespread implementation of this attractive technology. The main challenges in the application of these oxides in SOFCs are difficult sintering and insufficient conductivity in real cells. In this study, we propose a novel method to significantly enhance the performance of a yttrium-doped barium cerate proton conductor as an electrolyte for SOFCs through a Pd ingress–egress approach to the development of BaCe0.8Y0.1Pd0.1O3-d (BCYP10). The capability of the Pd egress from the BCYP10 perovskite lattice is demonstrated by H2-TPR, XRD, EDX mapping of STEM and XPS. Significant improvement in the sinterability is observed after the introduction of Pd due to the increased ionic conductivity and the sintering aid effect of egressed Pd. The formation of a B-site cation defect structure after Pd egress and the consequent modification of perovskite grain boundaries with Pd nanoparticles leads to a proton conductivity of BCYP10 that is approximately 3 times higher than that of BCY under a reducing atmosphere. A single cell with a thin film BCYP10 electrolyte reaches a peak power density as high as 645 mA cm-2 at 700 °C.